Pengembangan Multimedia Interaktif Articulate Storyline 3 pada Pembelajaran Bahasa Indonesia Menggunakan Model Problem Based Learning di Kelas IV Sekolah Dasar - Aulia, Bani Hasnatul; Desyandri, Desyandri (Lembaga Intelektual Muda Maluku, 2025)
The research aims to develop interactive multimedia Articulate Storyline 3 for Indonesian learning in grade IV of elementary school using the Problem Based Learning (PBL) model. The research uses the Research and Development (R&D) method with the ADDIE development model which includes five stages, namely Analysis, Design, Development, Implementation, and Evaluation. The trial subjects included 20 students from SDN 06 Pulai Anak Air, while the research subjects consisted of 27 students from SDN 01 Ladang Cakiah and 21 students from SDN 08 Campago Ipuh. Data collection was carried out through validation questionnaires involving material experts, linguists, and media experts, as well as practicality questionnaires filled out by teachers and students. The results showed that interactive multimedia obtained material validity of 92.5% (very valid), language validity of 85% (valid), and media validity of 97.5% (very valid). The practicality test reached 96.6% based on the teacher's response and 94.9% based on the student's response, both in the very practical category. The effectiveness test reached 91.06% with the category of very effective. The conclusion of the study is that the interactive multimedia Articulate Storyline 3 with the Problem Based Learning model is proven to be valid, practical, and effective to support the Indonesian learning process in grade IV of elementary school.